2018
DOI: 10.26451/abc.05.01.03.2018
|View full text |Cite
|
Sign up to set email alerts
|

Remembering past exchanges: Apes fail to use social cues

Abstract: -Nonhuman primates can remember events from their distant past. Furthermore, they can distinguish between very similar events by the process of binding. So far, research into long-term memory and binding has focused on the binding of contextual information, such as spatial surroundings. As such, we aimed to investigate if apes can bind and retrieve other types of information, specifically, social information. We presented great apes with three different object types; they learnt to exchange (via reinforcement)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…For instance, King (the gorilla) could remember what he had eaten and who had given him the food after a delay of 24 hr (Schwartz, Colon, Sanchez, Rodriguez, & Evans, 2002). However, a recent study by Lewis, Berntsen, and Call (2018) suggests that the who information must be salient to be successfully remembered, with apes failing to encode and remember who rewarded what, probably because the person was not a salient feature in the paradigm. This finding highlights the importance of carefully interpreting results in animal research in which subjects receive no instructions regarding what to attend to, and future research should clarify that a failure to remember is not just a failure to attend.…”
Section: Episodic-like Memory In Apesmentioning
confidence: 99%
“…For instance, King (the gorilla) could remember what he had eaten and who had given him the food after a delay of 24 hr (Schwartz, Colon, Sanchez, Rodriguez, & Evans, 2002). However, a recent study by Lewis, Berntsen, and Call (2018) suggests that the who information must be salient to be successfully remembered, with apes failing to encode and remember who rewarded what, probably because the person was not a salient feature in the paradigm. This finding highlights the importance of carefully interpreting results in animal research in which subjects receive no instructions regarding what to attend to, and future research should clarify that a failure to remember is not just a failure to attend.…”
Section: Episodic-like Memory In Apesmentioning
confidence: 99%
“…Perhaps because they do not form such enduring bonds with other individuals, rats base their decision to cooperate on the last encounter with their partner (using tit-for-tat like strategies) and not on the partner's overall level of cooperation 102 . Great apes remember past events for long periods of time 103,104 , but it is less clear how well and for how long they remember the social component of past events 105,106 . More studies requiring animals to encode social and non-social components of an event (especially a cooperative interaction) will further reveal the psychological basis of contingent cooperation in non-human animals.…”
Section: [H2] Monitoring Partnersmentioning
confidence: 99%
“…Clayton and Dickinson (1998) showed that scrub jays could recall the content of specific episodes (what-where-when information), a finding that has been replicated in numerous species (Babb & Crystal, 2006;Hoffman, Beran, & Washburn, 2009;Martin-Ordas, Haun, Colmenares, & Call, 2010). Other paradigms have investigated characteristics of episodic memory, such as temporal order (Schwartz, Hoffman, & Evans, 2005), free recall (Menzel, 1999), binding (Lewis, Berntsen, & Call, 2018;Martin-Ordas, Berntsen, & Call, 2013), spontaneous retrieval (Lewis, Call, & Berntsen, 2017b), distinctiveness (Lewis, Call, & Berntsen, 2017a), and unexpected recall (Zhou, Hohmann, & Crystal, 2012).…”
Section: Introductionmentioning
confidence: 95%